2005
DOI: 10.1103/physrevb.72.195337
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron mass in undopedCdTeCdMnTequantum wells

Abstract: Optically detected cyclotron resonance of two-dimensional electrons has been studied in nominally undoped CdTe/(Cd,Mn)Te quantum wells. The enhancement of carrier quantum confinement results in an increase of the electron cyclotron mass from 0.099m0 to 0.112m0 with well width decreasing from 30 down to 3.6 nm. Model calculations of the electron effective mass have been performed for this material system and good agreement with experimental data is achieved for an electron-phonon coupling constant α=0.32.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Indeed, due to the temperature-dependent Brillouin function in the second term of Eq. (9) the Zeeman splitting becomes comparable to the [61]. For the calculations we also used T Mn = T and literature data of T 0 = 0.8 K and S 0 = 2.2 for x = 0.015, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, due to the temperature-dependent Brillouin function in the second term of Eq. (9) the Zeeman splitting becomes comparable to the [61]. For the calculations we also used T Mn = T and literature data of T 0 = 0.8 K and S 0 = 2.2 for x = 0.015, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…There exist many parameters which affect on the effective mass of carriers in the CdTe-Cd 1−x Mn x Te MQWs, such as growth direction, well width, strain, polaron effect due to the electron-phonon interaction [19,20]. Equations (13) and (14) give only the dependence of the effective mass to composition and the effect of the other parameters is ignored.…”
Section: Resultsmentioning
confidence: 99%
“…In polar semiconductors, plasmon of free carriers intract with longitudinal optical (LO) phonon via macroscopic electric field. Due to the effect of the LO phonon-plasmon coupling (polaronic effects) the frequencies of the LO phonons are shifted [9,22] and allow the determination of the free carrier concentration and it is the only significant effect of the plasmon on the phonon response. The experimental results have shown that the polaronic effects on the effective mass of MQWs are reduced in comparison with the results for the bulk semiconductor [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Cadmium sulfide (CdS) is a II-VI semiconductor made of strong ionic bonding between Cd and S. An electron or an exciton in CdS is highly possible to be coupled to phonons due to the relatively large Froehlich coupling constant of 0.53, which is much larger than that of CdTe, GaAs, and GaP. [10,11] As can be seen in Figure 3, the Raman scattering intensity ratio of the 2LO and the 1LO of the CdS NWs is much larger than that of the CdS film, indicating strong resonance two-phonon coupling and excitonic scattering in the CdS NWs. [1] For CdS, the atomic masses of Cd and S have a relatively large difference.…”
Section: Introductionmentioning
confidence: 99%